Critical points and the presence of pathogenic bacteria in iced beverage processing lines - Nababan, Halim; Rahayu, Winiati Pudji; Waturangi, Diana Elizabeth; Suratmono, Suratmono; Puspitasari, Rina; Indrotristanto, Nugroho; Nikastri, Eva; Yuliangsih, Suci; Pusparini, Novi (The Journal of Infection in Developing Countries, 2017)
Introduction: Ice can be contaminated by pathogenic bacteria. This study aimed to identify critical points in iced beverage production and distribution lines to examine the presence of pathogenic bacteria in a beverage and its processing environment, as well as when water and ice used as main ingredients. Methodology: The critical points were determined using the principles of Hazard Analytical Critical Control Point (HACCP) to analyze each processing and distribution step from the survey. Samples collected from the points of concern based on the critical points that were found were tested for pathogens by conventional method and molecular method using primers and polymerase chain reaction (PCR). Results: Escherichia coli was found in 6.34% of samples, and 0.7% of them were confirmed as enterotoxigenic Escherichia coli (ETEC) by PCR. Vibrio cholerae was found in in 0.7% of water samples used to make iced beverages and in ice production, as well as in 2.12% of distribution and production tools. Salmonella Typhimurium was found in 1.4% of water samples used to make ice and ice products. Staphylococcus aureus was found in 2.02% of the surfaces of ice distribution and production tools and in 5.05% of production and distribution workers’ hands. S. aureus counts ranged from 2.4×102 - 3.5×102 colonies/100 cm² surface area and 1.9×10¹ - 3.7×102 colonies/workers’ hands. Conclusion: Control on many critical points in iced beverage processing and distribution is required so that the beverages are safe for consumption.